Faktor-Faktor yang Berhubungan dengan Perilaku Membaca Label Informasi Gizi - Sinaga, Christoper; Simanungkalit, Sintha Fransiske (Jurnal Endurance, 2019)
Nutritional information labels have an important role in the selection of healthy foods (Signal, 2007). BPKN of year 2013 states the behavior of reading nutrition information labels in indonesia only 7,9%. This study was conducted to determine the factors associated with reading nutritional information label behavior in Sekolah Menengah Kejuruan Farmasi Harapan Massa Depok of year 2018. This study used a cross sectional study design. Sample amounted to 98 respondents taken data with stratified random sampling methode. Bivariate results showed that there were a significant relationship between reading behavior of nutrition information label with gender (p-value: 0,019) and attitude (p-value: 0,019). While the employment status of father (p-value: 0,521) and knowledge of nutrition information label (p-value: 0,172) was not significant. Gender and student attitude related to nutritional information label reading behavior. The suggestion from this study was this school can be given counseling through printed media, lectures, and discussions related to the benefits of reading nutrition information labels Label informasi gizi memiliki peranan penting dalam pemilihan makanan yang sehat (Signal, 2007). BPKN (Badan Perlindungan Konsumen Nasional) tahun 2013 menyatakan perilaku membaca label informasi gizi di Indonesia hanya sebesar 7,9%. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan perilaku membaca label informasi gizi di Sekolah Menengah Kejuruan Farmasi Harapan Massa Depok tahun 2018. Penelitian ini merupakan penelitian deksriptif analitik. Sampel berjumlah 98 responden dengan penarikan sampel menggunakan metode stratified random sampling. Penelitian ini menunjukkan bahwa terdapat hubungan yang bermakna antara perilaku membaca label informasi gizi dengan jenis kelamin (p-value: 0,019) dan sikap (p-value: 0,019). Sementara itu status pekerjaan ayah (p-value: 0,521) dan pengetahuan label informasi gizi (p-value: 0,172) tidak bermakna. Jenis kelamin dan sikap siswa/i berhubungan dengan perilaku membaca label informasi gizi. Kesimpulan  peneliti sekolah perlu diberikan penyuluhan media cetak, ceramah, dan diskusi terkait manfaat dan pentingnya membaca label infromasi gizi.